Qualitative documentary analysis of guidance on information provision and consent for the introduction of innovative invasive procedures including surgeries within NHS organisations' policies in England and Wales. Issue 9 (1st September 2022) - Ochieng, Cynthia A; Richards, Hollie; Zahra, Jesmond; Cousins, Sian; Elliott, Daisy; Wilson, Nicholas; Paramasivan, Sangeetha; Avery, Kerry N L; Mathews, Johnny; Main, Barry G; Hinchliffe, Robert; Blencowe, Natalie S; et al.
Abstract : Objective: To review guidance, included in written local UK National Health Service (NHS) organisation policies, on information provision and consent for the introduction of new invasive procedures- including surgeries, and devices (IPs/Ds). Design: A qualitative documentary analysis of data on patient information provision and consent extracted from policies for the introduction of IP/Ds from NHS organisations in England and Wales. Setting: NHS trusts in England and health boards in Wales, UK. Participants: Between December 2017 and July 2018, 150 acute trusts in England and 7 health boards in Wales were approached for their policies for the introduction of new IP/Ds. In total, 123 policies were received, 11 did not fit the inclusion criteria and a further policy was included from a trust website resulting in 113 policies included for review. Results: From the 113 policies, 22 did not include any statements on informed consent/information provision or lacked guidance on the information to be provided to patients and were hence excluded. Consequently, 91 written local NHS policies were included in the final dataset. Within the guidance obtained, variation existed on disclosure of the procedure's novelty, potential risks, benefits, uncertainties, alternative treatments and surgeon's experience. Few policies stated that clinicians should discuss the existing evidence associated with a procedure. Additionally, while the majority of policies referred to patients needing written information, this was often not mandated and few policies specified the information to be included. Conclusions: Nearly a fifth of all the policies lacked guidance on information to be provided to patients. There was variability in the policy documents regarding what patients should be told about innovative procedures. Further research is needed to ascertain the information and level of detail appropriate for patients when considering innovative procedures. A core information set including patients' and clinicians' views is required to address variability around information provision/consent for innovative procedures.